Search for D[ast](2007)0 → μ+ μ− in B− → π− μ+ μ− decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; De Cian, Michel; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (The European physical journal. C, Particles and fields, 2023)
The very rare D∗(2007)0 → μ+ μ− decay is searched for by analysing B− → π− μ+ μ− decays. The analysis uses a sample of beautymesons produced in proton-proton collisions collected with the LHCb detector between 2011 and 2018, corresponding to an integrated luminosity of 9 fb−1. The signal signature corresponds to simultaneous peaks in the μ+ μ− and π− μ+ μ− invariant masses. No evidence for an excess of events over background is observed and an upper limit is set on the branching fraction of the decay at B(D∗(2007)0 → μ+ μ−) < 2.6 × 10−8 at 90% confidence level. This is the first limit on the branching fraction of D∗(2007)0→ μ+ μ− decays and the most stringent limit on D∗(2007)0 decays to leptonic final states. The analysis is the first search for a rare charm-meson decay exploiting production via beauty decays.
Im Titel ist [ast] als Tropfensternchen dargestellt
Im Titel sind das Plus- und Minuszeichen sowie [ast] und die Zahl 0 hochgestellt
*LHCb collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, M. De Cian, G. Frau, D. Gerick, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, J. Marks, M.P. Morgenthaler, G. Tuci, D.J. Unverzagt, U. Uwer, C. Witola, Y. Zhao, A. Zhelezov (und sehr viele weitere Personen)
Gesehen am 22.05.2024